Parallel Database Systems: The Future of Database Processing or a Passing Fad? - Gray, Jim; DeWitt, David J. (Institute of Electrical and Electronics Engineers, Inc., 1990)
Parallel database machine architectures have evolved from the use of exotic hardware to a software parallel dataflow architecture based on conventional shared-nothing hardware. These new designs provide impressive speedup and scaleup when processing relational database queries. This paper reviews the techniques used by such systems, and surveys current commercial and research systems.